Validating the Extended Software Process Assessment and Certification Model through Focus Group - Farvin Packeer Mohamed, Shafinah; Baharom, Fauziah; Deraman, Aziz; Yusof, Yuhanis (International Journal of Engineering and Technology, 2018)
Rapid growths of computers, mobile phones and Internet technology have created ways for irresponsible people to undertake computer crimes. Millions of users across the globe have fallen as victims to computer crimes, including Malaysia. It is because of current programming condition which is progressively mind boggling, dispersed, keeps classified information and effectively presented to malevolent assaults. Therefore, secure programming process is progressively increasing much significance among programming professionals and specialists. Be that as it may, just couple of studies were led in exploring its present practice in the product business, particularly in Malaysia. Along these lines, an exploratory examination is led among programming experts in Malaysia to consider their encounters and practices on the protected programming process in reality extends. This paper examines the discoveries from the examination, which included 93 programming specialists. Organized survey is used for information gathering reason while factual techniques, for example, recurrence, mean, and cross arrangement are utilized for information investigation. Results from this examination uncover that product professionals are winding up progressively mindful on the significance of secure programming process, nonetheless, they absence of proper execution of the practices.Â Â